Efficacy of some Sudanese Medicinal Plants Extracts to Remove Heavy Metals from Water - M., Ghada; A. I., Najla; M. H., Sajad; A., Fida; M. S., Eltohami; Nour, A. H.; Elhassan, Hajo Elzein; Elsaman, Tilal (AENSI Publishing, 2017)
Some heavy metals have bio-importance as trace elements but, the biotoxic effects of many of them in human are of great concern.Although several adverse health effects of heavy metals have been known for a long time, exposure to heavy metals continues, and is even increasing in some parts of the world, particularly in less developed countries. The main threats to human health from heavy metals are associated with exposure to lead, cadmium, mercury and arsenic. The use of certain whole plants and plant extracts is reported to possess an ability to serve in water purification.The main objectives of this study are to test certain sudanese plants ethanolic extracts namely; Moringaoleifera, Typhalatifolia and Cymbopogonproxmus for their ability to purify water from cadmium, zinc, chromium and lead. Analysis of the heavy metals cadmium, chromium, lead and zinc were performed before and after treatment of water with the extracts. The findings showed that ethanolic extracts of M. oleifera, T.latifolia and C.proxmus were capable of absorbing the chromium, cadmium and zinc. Lead metal absorbed by T.latifoliaand C.proxmusethanolic extracts and the extract of M. oleifera didn’t absorb this metal. It can reasonably conclude that, all tested ethanolic plants extracts had capability to remove such metals also this finding confirm the traditional use of these plants in water purification.Therefore, a wide investigation of these plants for their removal potent of heavy metals and the identification of the phytochemicals of these plants would be an interesting line of inquiry.